The Implications of Islamic Law on the Rights of Religious Minorities in Muslim-Majority Countries - Karimullah, Suud Sarim (MILRev: Metro Islamic Law Review, 2023)
This study aimed to explore the complex implications of Islamic law on the rights of religious minorities in Muslim-majority countries. Through a comprehensive literature analysis, the study summarized information from various relevant text sources. The findings show the complex challenges faced by religious minorities when exercising the rights in Muslim-majority countries. Examining the impact of Islamic law on religious minorities' rights suggests that the legislation could provide a potential basis for protection. However, the interpretation and application of the law varies between countries. Introducing Islamic law into state policies often creates tensions between religious and universal human rights principles, requiring careful efforts to strike a delicate balance. In modern contexts, such as the impact of globalization and information technology, Muslim-majority countries are faced with challenges that prompt constant adaptation to ensure the effective protection of religious minorities’ rights. Therefore, addressing these challenges requires a comprehensive method including legal reform, interreligious dialogue, and community education to ensure that the rights of religious minorities are respected and substantially protected.